Barriers to Multiculturalism: In-Group Favoritism and Out-Group Hostility Are Independently Associated With Policy Opposition. Issue 1 (January 2018) - Perry, Ryan; Priest, Naomi; Paradies, Yin; Barlow, Fiona Kate; Sibley, Chris G.
Bias in favor of the in-group is a key determinant of discrimination and is thought to be largely independent of, and qualitatively distinct from, out-group hostility. One key difference, according to realistic conflict theory, is that in-group preferences become more closely associated with discrimination when intergroup threat is salient. The current study presents a direct comparison of the level of association of in-group favoritism and out-group hostility with opposition to multiculturalism policies in New Zealand. With both predictors operationalized as affect ratings of warmth and anger across separate models, in-group favoritism and out-group hostility were independently associated with European New Zealanders' ( N = 10, 869) opposition to both resource-specific and symbolic policies. Furthermore, in-group favoritism was more strongly associated with opposition to resource-specific policies that represent high realistic threat (compared with symbolic policies). In contrast, out-group hostility was more consistently associated with both policy domains.